A low-cost photoacoustic microscopy system with a laser diode excitation - Wang, Tianheng (Biomed Opt Express, 2014)
Photoacoustic microscopy (PAM) is capable of mapping microvasculature networks in biological tissue and has demonstrated great potential for biomedical applications. However, the clinical application of the PAM system is limited due to the use of bulky and expensive pulsed laser sources. In this paper, a low-cost optical-resolution PAM system with a pulsed laser diode excitation has been introduced. The lateral resolution of this PAM system was estimated to be 7 µm by imaging a carbon fiber. The phantoms made of polyethylene tubes filled with blood and a mouse ear were imaged to demonstrate the feasibility of this PAM system for imaging biological tissues.